A theoretical analysis of mechanical and durability enhancement of circular reinforced concrete columns repaired with UHPC. (15th April 2020) - Farzad, Mahsa; Sadeghnejad, Amir; Rastkar, Siavash; Moshkforoush, Arash; Azizinamini, Atorod
Highlights: A simplified formula is proposed to predict the capacity of UHPC repaired section. The formula has been validated by experimental data. The extended life span of columns repaired with UHPC is estimated. Abstract: Ultra-high performance concrete (UHPC) has been promoted as a strong, durable construction material which can provide a barrier to corrosion due to its low permeability, and can thus be an ideal durable repair strategy for corrosion management. A UHPC based solution to enhance the mechanical strength of axially-loaded, sub-structural reinforced concrete elements, was proposed and experimentally investigated in an earlier study by the authors. The results recommended that depending on the UHPC shell thickness, this repair method may cause shifting of the critical section, which should be a design consideration. In this paper, the effect of the UHPC shell thickness on structural performance and durability of the retrofitted structure was numerically investigated. A well-established numerical sectional analysis method was utilized to estimate the capacity of the repaired section of prototype bridge columns with varying UHPC shell thicknesses, and a simplified method for predicting the structural enhancement of UHPC repair was proposed. Furthermore, analytical models were developed to predict the service life of the repaired sections by calculating the time required for chloride ions to reach the surface of the reinforcement.